Building Digital Designer Portfolio Using Web Publishing Tools - Shkatova, Iulia; Dědic, Filip; Chabirova, Majja; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This Bachelor thesis is aimed to assist designers in building a digital portfolio using web publishing tools. The goal of the thesis is first to define the rules for building a successful digital portfolio and second to practice in building one using selected web publishing tool. The theoretical part includes an overview on digital design, design process and the concept of design portfolio. Theoretical sources are enriched with face-to-face interviews with Ales Nesetril, who is a product designer at STRV and Majja Chabirova, who is a freelance game concept artist. The analytical part compares the most popular web publishing tools used by designers: Wix, Squarespace, Readymag, Tilda and Cargo Collective. Obtained knowledge is implemented in the practical part, which covers the process of building personal portfolio using Readymag web publishing tool. The outcome of the thesis is a functional personal portfolio, in which a designer can make changes anytime without asking for help. This thesis will be mainly useful to junior designers and recent graduates building an online portfolio. However, it will also offer more experienced designers valuable advice on enhancing their online presence. Non-designers will learn how to create an online publication.
Vedoucí práce: Filip Dědic
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses